Variability of wastewater discharge from a selected sewage system in Jaworzno - Krzysztof Chmielowski (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of the paper was to analyze the influence of atmospheric precipitation on the variability of wastewater outflow from a selected sewerage system in southern Poland. The research period was the years 2011-2016. The daily outflows of wastewater from the sewerage system were used.